2020
DOI: 10.1021/acs.jpcc.9b11241
|View full text |Cite
|
Sign up to set email alerts
|

Composites of Poly(3,4-ethylenedioxythiophene) and CoFe2O4 Nanoparticles: Composition Influence on Structural, Electrical, and Magnetic Properties

Abstract: Composites of magnetic CoFe 2 O 4 nanoparticles (MNP) in a Poly (3,4-ethylenedioxythiophene) matrix at different ratios have been synthetized. Composites were characterized by electron microscopy, X-ray diffraction, thermal analysis, electrical conductivity, magnetization and magnetoresistance studies. In the composites the MNP appear clustered, with an interparticle distance essentially constant, but where two regimes are distinguished for cluster separation: for high MNP concentrations an intercluster sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 74 publications
3
21
0
Order By: Relevance
“…A comparison of literature reports with the magnetic parameters of our calcined CoFe 2 O 4 demonstrates the efficacy of our approach (Table S2). ,,,, ,,, …”
Section: Resultsmentioning
confidence: 99%
“…A comparison of literature reports with the magnetic parameters of our calcined CoFe 2 O 4 demonstrates the efficacy of our approach (Table S2). ,,,, ,,, …”
Section: Resultsmentioning
confidence: 99%
“…These hybrid composites are part of a new generation of smart materials, 18 and those based on PEDOT have been proposed for applications in catalysis, magnetic field sensors, microwave absorption, ion adsorption, and antibacterial agents, among others. 19–23…”
Section: Introductionmentioning
confidence: 99%
“…There are few works that report the influence of the composite composition on the physicochemical properties of these materials. 19,22,24–27 For example, Ohlan et al 22 synthesized and characterized PEDOT-barium ferrite nanocomposites with different compositions. They found that these materials have strong microwave absorption properties, which depend on the barium ferrite concentration in the polymer matrix, and a shielding effectiveness that increases with the ferrite content.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these contaminants are pharmaceuticals, personal care products, pesticides, disinfection by-products, and synthetic chemicals such as dyes [ 3 ]. The list is ever-expanding due to an advanced instruments to detect contaminants in water bodies and by-product formed during wastewater treatment processes [ 4 ] in the concentrations range of μg/L to ng/L [ 5 ]. Organic dyes are non-biodegradable, highly toxic to aquatic organism, and carcinogenic to humans.…”
Section: Introductionmentioning
confidence: 99%